Need Analysis Of â€œSi Ecoâ€ Ethno-Confidence Game for Slow Learner Students - Sekar Dwi Ardianti; Savitri Wanabuliandari; Esti Wijayanti (Universitas Pendidikan Ganesha, 2021)
ABK students are students who have different characteristics from students in general. One of the ABK is a slow learner. Slow learner students have a tendency to not be confident. Therefore, it is necessary to develop the â€œSI ECOâ€ game to help slow learner students overcome the crisis of confidence. The purpose of this studyÂ to analyze the need for developing media of ethno-confidence â€œSI ECOâ€ game for slow learner students. This research method is descriptive quantitative method. The subjects of this study were 2 teachers and 26 students. The data in this study are in the form of questionnaires and interviews with teachers and students. Data collection techniques using interviews, questionnaires and document studies. Data analysis was carried out descriptively by percentage. The results of the questionnaire of slow learner students have confidence in the criteria of lack of confidence. The results of the student needs questionnaire showed that there was a need for slow learner students for learning media in the form of games with ethno content that could foster self-confidence. The results of interviews with teachers show that the availability of learning media that incorporates cultural elements is still very limited so that the development of learning media in the form of the ethno-confidence game